Evidence that a distribution of bacterial reaction centers underlies the temperature and detection-wavelength dependence of the rates of the primary electron-transfer reactions. - Kirmaier, C (1990)
The rates of the primary electron-transfer processes in Rhodobacter sphaeroides reaction centers have been examined in detail by using 150-fs excitation flashes at 870 nm. At room temperature the apparent time constants for both initial charge separation (P* --> P+BPhL-) and subsequent electron transfer (P+BPhL- --> P+QA-) are found to encompass a range of values (approximately 1.3-4 ps and approximately 100-320 ps, respectively), depending on the wavelength at which the kinetics are followed. We suggest this reflects a distribution of reaction centers (or a few conformers), having differences in factors such as distances or orientations between the cofactors, hydrogen bonding, or other pigment-protein interactions. We also suggest that the time constants observed at cryogenic temperatures (approximately 1.3 and approximately 100 ps, respectively, with much smaller or negligible variation with detection wavelength) do not reflect an actual increase in the rates with decreasing temperature but rather derive from a shift in the distribution of reaction centers toward those in which electron transfer inherently occurs with the faster rates.